Hi friends,

I have a following equation :

x = x^{2}- [(N-1) * 2], where N = 11

that becomes:

x = x^{2}- (20)

My question:

If possible, how can we derive the value ofxin the equationx = x?^{2}- (20)

Thanks in advance,

Regards.

Printable View

- Jun 16th 2012, 11:21 PMbytelogikEquation simplification
Hi friends,

I have a following equation :

**x = x**^{2}- [(N-1) * 2], where N = 11

that becomes:

**x = x**^{2}- (20)

My question:

If possible, how can we derive the value of**x**in the equation**x = x**?^{2}- (20)

Thanks in advance,

Regards. - Jun 17th 2012, 12:38 AMProve ItRe: Equation simplification